The role of transforming growth factor β in upper gastrointestinal cancers: A systematic review. (November 2021) - Veen, Linde M.; Skrabanja, Tim L.P.; Derks, Sarah; de Gruijl, Tanja D.; Bijlsma, Maarten F.; van Laarhoven, Hanneke W.M.
Graphical abstract: Schematic overview of the effect of transforming growth factor β (TGF-β) in gastric and esophageal cancer. VEGF = vascular endothelial growth factor, HLA-G = human leukocyte antigen G, MMT = mesothelial-to-mesenchymal transition, Treg = regulatory T cell. A red highlight denotes a tumor-promoting effect, a green highlight shows a tumor-suppressing effect and a grey highlight indicates no effect of TGF-β. Highlights: TGF-β can act as both a tumor promotor and tumor suppressor in esophageal and gastric cancer. The tumor promoting role of TGF-β is most evident in this review. Additional research is needed to identify patients who would benefit from targeted therapy. Abstract: Esophageal and gastric malignancies are associated with poor prognosis, in part due to development of recurrences or metastases after curative treatment. The transforming growth factor β (TGF-β) pathway might play a role in the development of treatment resistance. In this systematic review, we provide an overview of preclinical studies investigating the role of TGF-β in esophageal and gastric malignancies. We systematically searched MEDLINE/PubMed and EMBASE for eligible preclinical studies describing the effect of TGF-β or TGF-β inhibition on hallmarks of cancer, such as proliferation, migration, invasion, angiogenesis and immune evasion. In total, 2107 records were screened and 45 articles were included, using mouse models and 45 different cell lines. TGF-β failed to induce apoptosis in twelve of sixteen tested cell lines. TGF-β could either decrease (five cell lines) or increase proliferation (seven cell lines) in gastric cancer cells, but had no effect in esophageal cancer cells. In all esophageal and all but two gastric cancer cell lines, TGF-β increased migratory, adhesive and invasive capacities. In vivo studies showed increased metastasis in response to TGF-β treatment. Additionally, TGF-β was shown to induce vascular endothelial growth factor production and differentiation of cancer-associated fibroblasts and regulatory T-cells. In conclusion, we found that TGF-β enhances hallmarks of cancer in most gastric and esophageal cancer cell lines, but not in all. Therefore, targeting the TGF-β pathway could be an attractive strategy in patients with gastric or esophageal cancer, but additional clinical trials are needed to define patient groups who would benefit most.